ANALISIS NILAI-NILAI EDUKATIF DALAM PRILAKU TOKOH GEORGE PADA SERIAL PENDEK FILM CURIOUS GEORGE - Balqis, Rania; Asy Syifa, Rifqah; Ningcahya Ningsih, Sal Sabila; Agustina, Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The animated movie Curious George serves as a valuable educational resource for young viewers. George, the central character, is depicted as a highly inquisitive, energetic, and adventurous figure throughout his various activities. This study seeks to examine the educational messages conveyed through George's behavior, particularly in the holiday episode, using a qualitative content analysis approach to observe his actions and interactions on screen. The findings reveal that George's conduct reflects a wide range of learning values, such as a spirit of exploration, creative thinking, problem-solving abilities, self-reliance, and hands-on experiential learning. Furthermore, his adventurous nature mirrors the way children naturally learn by engaging with and responding to the world around them. These results suggest that Curious George holds strong potential as an engaging and context-based educational tool for fostering positive learning values in young children.